The Position of English in the Linguistic Schoolscapes in an Indonesian Islamic Boarding School - Eliawati, Deni; Ngadiso, Ngadiso; Putra, Kristian Adi (Pusat Pelatihan, Riset, dan Pembelajaran Bahasa, 2024)
The choice of use of languages ​​in schools, including in the linguistic schoolscapes, represents the contestation of language identities, ideologies, and power. This study looks at the position of English, as opposed to Indonesian, Arabic, and Javanese, in the linguistic schoolscapes in an Indonesian Islamic boarding school in Central Java. A descriptive qualitative method and the theoretical framework of language planning and policy (Spolsky, 2004) are used to analyze the data. The findings show that Javanese and Indonesian are used in daily communication. English and Arabic are taught in the language program. In the signs at the boarding school, English is the second language to be used frequently at the linguistic school cape, after Indonesian, while Javanese, as the students' everyday language, is far behind. The implication of the linguistic school landscape finding in this research is that foreign languages ​​such as English, Arabic, and others considered necessary have the potential to become a new development in language teaching and learning.